O preço das commodities importa? Eficiência operacional dos bancos brasileiros e a queda recente nos preços das commodities - Lima, Gilmar Alves (2017)
This work analyzes the effect of the recent drop in commodity prices, starting from march 2014, on the level of efficiency of Brazilian banks. The core target of this paper is to observe whether, in general, adverse shocks tend to make banks more efficient due to the restrictions that these situations impose. For this investigation, it was necessary to collect the data from the Brazilian conglomerates and independent financial institutions (except for development banks) from March 2011 to September 2016. The Risk Weighted Assets - RWA related to the exposure due to the variation of commodity prices (RWACOM) were used to ascertain the exposure to commodities throughout this time. The results indicate that the recent drop in commodity prices did not influence the gain or loss of efficiency of Brazilian banks more exposed to price changes.